(untitled) (Communications in Computational Physics, 2018)
A fluid mixture model of tissue deformations has been studied in this paper. The model is a mixed system of nonlinear hyperbolic and elliptic partial differential equations. Both theoretical linear stability and numerical analysis are presented. Comparisons between standard numerical methods that utilize Runge-Kutta methods coupled with the WENO scheme and the immersed interface methods are given. Numerical examples are also presented.